Analisis Pengaruh Total Quality Management terhadap Kinerja Operasional pada Industri Putra Bali Rattan Furniture di Kecamatan Mayang Kabupaten Jember - Ma'rifah, Nurul; Supeni, Retno Endah; Wibowo, Yohannes Gunawan (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to analyze the effect of total quality management with 4 indicators, namely customer satisfaction, employee empowerment, continuous quality improvement, and management based on facts on operational performance at the Putra Bali Rattan Furniture Industry in Mayang District, Jember Regency. This research is research using a combination approach (mix methods). A sample of 65 respondents was obtained using a saturated sampling technique. Data was obtained using questionnaires and interviews with the owner and 5 consumers and then analyzed using regression analysis. In processing research data, researchers used the SPSS version 22 application. The research results show that 3 of the 4 X variables, namely customer satisfaction, employee empowerment, and continuous quality improvement have a positive and significant effect on operational performance. Meanwhile management variables based on facts have a negative effect on operational performance. The positive influence of the customer satisfaction variable is also supported by the results of interviews which state that the company has implemented 4 indicators of customer satisfaction and in line with this, operational performance has also increased. In conclusion, customer satisfaction, employee empowerment, and continuous quality improvement have a positive and significant effect on operational performance, while management based on facts has a negative effect. Keywords: Customer Satisfaction, Employee Empowerment, Management Based on Facts, Operational Performance , Quality Improvement Sustainable